Photocontrollable PROTAC molecules – structure and mechanism of action - Koravović, Mladen; Tasić, Gordana; Rmandić, Milena; Marković, Bojan (Archives of Pharmacy, 2021)
Traditional drug discovery strategies are usually focused on occupancy of binding sites that directly affect functions of proteins. Hence, proteins that lack such binding sites are generally considered pharmacologically intractable. Modulators of protein activity, especially inhibitors, must be applied in appropriate dosage regimens that often lead to high systemic drug exposures in order to maintain sufficient protein inhibition in vivo. Consequently, there is a risk of undesirable off-target drug binding and side effects. Recently, PROteolysis TArgeting Chimera (PROTAC) technology has emerged as a new pharmacological modality that exploits PROTAC molecules for induced protein degradation. PROTAC molecule is a heterobifunctional structure consisting of a ligand that binds a protein of interest (POI), a ligand for recruiting an E3 ubiquitin ligase (an enzyme involved in the POI ubiquitination) and a linker that connects these two. After POI-PROTAC-E3 ubiquitin ligase ternary complex formation, the POI undergoes ubiquitination (an enzymatic post-translational modification in which ubiquitin is attached to the POI) and degradation. By merging the principles of photopharmacology and PROTAC technology, photocontrollable PROTACs for spatiotemporal control of induced protein degradation have recently emerged. The main advantage of photocontrollable over conventional PROTACs is the possible prevention of off-target toxicity thanks to local photoactivation.